2016
DOI: 10.1289/ehp.1509756
|View full text |Cite
|
Sign up to set email alerts
|

Health Impacts of Climate Change in Pacific Island Countries: A Regional Assessment of Vulnerabilities and Adaptation Priorities

Abstract: Background:Between 2010 and 2012, the World Health Organization Division of Pacific Technical Support led a regional climate change and health vulnerability assessment and adaptation planning project, in collaboration with health sector partners, in 13 Pacific island countries—Cook Islands, Federated States of Micronesia, Fiji, Kiribati, Marshall Islands, Nauru, Niue, Palau, Samoa, Solomon Islands, Tonga, Tuvalu, and Vanuatu.Objective:We assessed the vulnerabilities of Pacific island countries to the health im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 32 publications
3
133
0
3
Order By: Relevance
“…In the Pacific Islands, where diarrhoea is the most significant water-borne disease and ENSO has marked impacts on climate, there is a paucity of evidence for explicit El Niño-diarrhoea associations, although this is implied in a number of studies [80][81][82]. For West Africa, de Magny et al [83] suggested associations of diarrhoea with El Niño where ENSO, via the so-called Indian Oscillation and associated variations in large scale rainfall and temperature fields, may well influence cholera dynamics and thus diarrhoea.…”
Section: Diarrhoeamentioning
confidence: 99%
“…In the Pacific Islands, where diarrhoea is the most significant water-borne disease and ENSO has marked impacts on climate, there is a paucity of evidence for explicit El Niño-diarrhoea associations, although this is implied in a number of studies [80][81][82]. For West Africa, de Magny et al [83] suggested associations of diarrhoea with El Niño where ENSO, via the so-called Indian Oscillation and associated variations in large scale rainfall and temperature fields, may well influence cholera dynamics and thus diarrhoea.…”
Section: Diarrhoeamentioning
confidence: 99%
“…migrant workers and socioeconomically stressed populations). (4) The issue of climate change is bigger than the worldwide spread of the Zika virus. It has been stated: "What were those of the past thinking and doing to put us in this environmental situation?"…”
mentioning
confidence: 99%
“…Investigators now report that Pacific island countries including Fiji, Tonga, and the Marshall Islands are among the nations most vulnerable to climate-related health problems due to their particular geographic, demographic, and socioeconomic characteristics 2 . Their new paper is a synthesis of the key technical findings and policy implications of the 2015 World Health Organization report Human Health and Climate Change in Pacific Island Countries , written by the same group 3 …”
mentioning
confidence: 99%